(3GdZQQ GdHgjI aj TQM GdHgLI GdhQOjIs - (3RcQjG Hf eMeO Hf CMeO Hf RcQjG GdCfUGQj GdSfjcj GdeUQj GdTGaYqj, CHh jMji , J (B926 (3g` s ((3YHO GdQMef Hf CMeO Hf eMeO GdHWjfi GdTGaYi s)
(3ChdgG (B:s
(3HGH GdfcGM gh dZI GdVe s
(3BNQgG (B:s
(3Je GdLRA GdKGdK HMeO Gddg hYhfg hMSf Jhajbg s
(3Vef eLehY , JQJjHgG (B: 1s
(3GdcJGH GdeTQhM(B: (3GdHgLI GdhQOjI ai fXe GdMGhi GdUZjQ dRjf GdOjf YeQ Hf eXaQ GdhQOi GdTGaYi J (B749s
(3GdfSNI HgG MhGTs
(3GdfSNI efbhdI Yf fSNI bhHdJ HNW eDdag ceG ai BNQgs
(3HgG fXGe GdJYbjHI s
(3QGLY LRA BNQ ef GdfSNI (B-(3heYdheGJ GdfSN(B- (3aj fSNI(B:2/89 (3chjJ s
(3bQf GdfSN (B:s
Keywords: (3Gdabg GdTGaYjs